Evaluasi Kesejahteraan Sekolah dengan Pendekatan Model Sekolah Sejahtera di SMP 24 Malang - Prasetyo, Yoyok Bekti (Universitas Muhammadiyah Yogyakarta, 2010)
One of model that can be developed on school health programs is The School Well-being Model. Indicators prosperous school includes four dimensions: school conditions (having), social relationships (loving), the mean self-fullfiment (being), and health status. This study aims to evaluate the condition of SMP 24 Malang based welfare indicators of The School WellÂ¬being Model. Descriptive research design was to determine the school prosper with school welfare conditions. Data collection using the School Health Promotion Survey (SHPS). The condition of SMP 24 Malang is a dusty (73.3%) and noise (61.9%). There are difficulties in doing the task group students (71.3%) and interact with friends (55.5%). There are difficulties in preparing for the exam students (51.8%) and homework (32.8%). Perceived health problems in the past month is feeling tired and weak (42.1%), headache (36.8%) and, insomnia (23.9%). Health promotion schools that need it suggests the hearing conversation program, counseling programs, measures to reduce physical and psychological stress.Salah satu model yang dapat dikembangkan pada program kesehatan sekolah adalah Model Sekolah Sejahtera (The School Well-being Model). Indikator sekolah sejahtera meliputi empat dimensi yaitu: school condition (having), social relationship (loving), mean self-fullfiment (being), dan health status. Penelitian ini bertujuan mengevaluasi kondisi kesejahteraan SMP 24 Malang berdasarkan indikator Model Sekolah Sejahtera. Desain penelitian adalah deskriptif untuk menentukan sekolah sejahtera dengan Kondisi kesejahteraan sekolah. Pengumpulan data menggunakan Survei Promosi Kesehatan Sekolah (School Health Promotion Survey/SHPS). Kondisi sekolah di SMP 24 Malang adalah berdebu (73,3%) dan suara bising (61,9%). Ada kesulitan siswa dalam mengerjakan tugas kelompok (71,3%) dan berinteraksi dengan teman (55,5%). Ada kesulitan siswa dalam mempersiapkan ujian (51,8%) dan mengerjakan pekerjaan rumah (PR) (32,8%). Masalah kesehatan yang dirasakan dalam sebulan terakhir adalah merasa lelah dan lemas (42,1%), sakit kepala (36,8%), sulit tidur (23,9%). Promosi kesehatan sekolah yang perlu disarankan adalah hearing conversation program, program konseling, tindakan untuk mengurangi stres fisik dan psikologis.